Real-world data suggest that geriatric assessment fails to stratify risk in treating older adults with lung cancer - Donadio, Mauro Daniel Spina; Oliveira, Audrey Cabral F; Moura, Luciana Leite; Jesus, Victor Hugo Fonseca de; Felisimino, Tiago Cordeiro; Dettino, Aldo Lourenço Abbade (Brazilian Journal of Oncology, 2021)
Introduction: Older adults require attention to risks of treatment toxicity. The purpose of this study was to evaluate epidemiological data and clinical outcomes of patients with lung cancer treated with non-curative intent assessed by geriatric assessment (GA) and restricted access to new therapies.Methods: We evaluated older adults with non-small cell lung cancer treated with palliative chemotherapy or first generation target therapy who underwent GA. Overall survival (OS) was calculated and we performed univariate and multivariate analysis to determine prognostic factors for OS.Results: Fifty-four patients aged ≥70 years had a median age of 76 years, 76% was classified as Katz A and 50% as Lawton <27. 68.5% were at risk of malnutrition or malnourished; 61.1% had ≥2 comorbidities. The mean OS was 17.1 months. In the univariate analysis, lower survival results were observed for patients with ECOG≥2 (HR=5.9; p<0.001), higher number of metastasis sites (HR=2.0; p=0.04) and liver metastasis (HR=12.6; p<0.001). In multivariate analysis, male gender, ECOG≥2, more than 2 metastatic sites and liver metastases were associated with higher risk of death. We did not observe differences in survival according to functional capacity.Conclusion: GA showed no prognostic relationship in our small population. Patients with ECOG≥2, more than 2 metastatic sites and hepatic metastasis presented higher risk of death. For the older population, new treatment modalities are fundamental and outweigh the prognostic importance of the clinical factors of GA.
Keywords: Geriatric assessment; Lung neoplasms; Frail elderly.